The Effect of NPK Fertilizer and Tofu Dregs Organic Fertilizer on The growth of Land Kale Plants (Ipomea reptans Poir) - Rayyana Rayyana; Ahmad Raksun; M. Yamin (Jurnal Biologi Tropis, 2023)
Tofu dregs have a fairly high protein content because not all of the protein content is decomposed during the production of tofu. Tofu dregs are not put to good use, in fact many people actually dispose of waste which causes environmental pollution. The aim of the study was to determine the effect of NPK fertilizer and tofu dregs organic fertilizer, as well as the combination of these fertilizers on the growth of ground water spinach (Ipomea reptans Poir). The type of research is an experimental 4x4 factorial with a completely randomized design. The first factor was NPK fertilizer which consisted of 4 levels (0, 0.4, 0.8 and 1.2 g/100 ml of water). The second factor was tofu dregs organic fertilizer (0, 50, 100, 150 g/3 kg soil) which consisted of 16 treatment combinations. Test the research hypothesis using TWO WAY ANOVA. The results showed that the application of NPK fertilizer and organic tofu dregs had an effect on fresh weight, plant height, dry weight, and number of leaves. However, it has no effect on leaf area. Application of organic tofu dregs fertilizer at a dose of 150 g/3 kg of soil, and NPK fertilizer 0.4 and 0.8 g/100 ml of water resulted in the best growth of kale plants at the age of 30 days.